Hydrothermal Alteration And Vein Types Of The Randu Kuning Porphyry Cu-Au Deposit At Selogiri Area, Wonogiri - Sutarto Sutarto; Arifudin Idrus; Sapto Putranto; Agung Harjoko; Lucas D Setijadji; Franz M Meyer; Rama Danny (Buletin Sumber Daya Geologi, 2014)
Many Tertiary hydrothermal altered dioritic composition intrusive rocks were found at the Randu Kuning area and its vicinity, Selogiri, including hornblende microdiorite, hornblende-pyroxene diorite and quartz diorite. The hydrothermal fluids which responsible for the alteration and mineralization at the area is associated with the occurence of the horblende microdiorite intrusion. The alteration zone at the Randu Kuning area and its vicinity can be divided intoseveral hydrothermal alteration zones, such as potassic (magnetite-biotite-K feldspar), prophyllitic (chlorite-magnetite-epidote-carbonate), phyllic (quartz-sericite-chlorite) and argillic (clay mineral-sericite). The alteration pattern in the Randu Kuning porphyry Cu-Au deposit is tipically a diorite model characterising by the domination of potassic alteration and prophyllitic zone. Phyllic and argillic alteration types are restrictive found within the fault zones. A lot of porphyry vein types were found and observed at the Randu Kuning area, and classified into at least seven vein types. The paragenetic sequence of those veins from theearliest to the latest respectively are 1). Magnetite-chalcopyrite±quartz-biotite veinlets, 2). Quartz±magnetite (A type) veins, 3). Banded/Laminated quartz-magnetite (M type) veins, 4). Quartz±K feldspar (B type)veins, 5). Quartz with thin centre line sulphide (AB type) veins, 6). Pyrite±chalcopyrite (C type) veinlets, and 7). Pyrite-quartz+chalcopyrire+carbonate (D type) veins. Gold and copper mineralisation of the Randu Kuning Porphyry Cu-Au deposit, mostly related to the presence of quartz veins/veinlets containing sulfide i.e. Quartz with thin centre line sulphide veins, Pyrite±chalcopyrite veinlets, and Pyrite-quartz+chalcopyrire+carbonate veins.